2016
DOI: 10.21307/jofnem-2017-009
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Concentrations of Trichoderma longibrachiatum and Cadusafos for Controlling Meloidogyne javanica on Zucchini Plants

Abstract: A factorial experiment was established in a completely randomized design to verify the effect of different inoculum levels of an Iranian isolate of Trichoderma longibrachiatum separately and in combination with various concentrations of cadusafos against Meloidogyne javanica in the greenhouse. Zucchini seeds were soaked for 12 hr in five densities (0, 10 5 , 10 6 , 10 7 , and 10 8 spores/ml suspension) of the fungus prior to planting in pots containing four concentrations of cadusafos (0, 0.5, 1, and 2 mg a.i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Some microorganisms act as phytopathogen controllers. This is the case for species of the genus Trichoderma, which parasitize and successfully control Sclerotinia [228,229], Fusarium [230], Verticillium [231], and Macrophomina [232] fungal species, among others, and show nematicidal activity against gall-forming Meloidogyne species [233][234][235]. In addition, the evaluation of functional traits of mycorrhizal, rhizospheric, or endophytic species has identified species with high potential to promote plant growth.…”
Section: Why Should We Know About Microbial Diversity?mentioning
confidence: 99%
“…Some microorganisms act as phytopathogen controllers. This is the case for species of the genus Trichoderma, which parasitize and successfully control Sclerotinia [228,229], Fusarium [230], Verticillium [231], and Macrophomina [232] fungal species, among others, and show nematicidal activity against gall-forming Meloidogyne species [233][234][235]. In addition, the evaluation of functional traits of mycorrhizal, rhizospheric, or endophytic species has identified species with high potential to promote plant growth.…”
Section: Why Should We Know About Microbial Diversity?mentioning
confidence: 99%
“…Trichoderma spp. parasitize and successfully control phytopathogenic fungal species such as Sclerotinia (Jones et al, 2014, 2016), Fusarium (Saravanakumar et al, 2016), Verticillium (Carrero-Carrón et al, 2016), and Macrophomina (Khaledi and Taheri, 2016), among others, and have nematicidal effect on the gall-forming Meloidogyne (Sahebani and Hadavi, 2008; Feyisa et al, 2016; Sokhandani et al, 2016). This functional characteristic of Trichoderma and other biocontrol species responds to the increasing call for practices that minimize the side effects left by pesticides, such as resistance in pest populations, reduction of soil and water quality, and the generation of residues with harmful effects on non-target organisms.…”
Section: Agricultural Technological Microbiologymentioning
confidence: 99%
“…Zhang et al, (2012) reported an isolate of T. longibrachiatum that had a strong lethal and parasitic effect on the J2s of Meloidogyne incognita at a concentration of 1.5 x 107 conidia/ml, inhibited and parasitized more than 88% J2 s in cucumber seedlings after 14 days. Sokhandani et al, (2016) showed that T. longibrachiatum concentrations at 108 conidia/mL suspension produced the best plant growth and reduced the reproduction of M. javanica. Several control measures like cultural practices, chemical and biological control are used to reduce the population of the nematode but unfortunately there are many problem associated with the use of chemical control.…”
Section: Introductionmentioning
confidence: 99%